Steering Gear Control System of Mechanical Arm Based on DSP - Yang Yang, Jilei Tang (Forest Chemicals Review, 2022)
This paper is based on the brushless DC motor mechanical arm steering gear control system design. The hardware uses DSP chip STM320F2812 (DSP2812 for short) as the processor, and the arm is composed of four joint steering gear and its supporting connection rod. The position sensor is used to collect and feedback the position signal, so as to realize the precise closed-loop control of the motion Angle of the steering gear, to realize the 4-DOF rotation control of the mechanical arm.The software of the system includes DSP2812 master control program, initialization program, A/D signal acquisition program, error calculation and control algorithm implementation program and PWM duty cycle calculation program.The operator can control the manipulator through the upper computer input instructions.